Analysis of the Istidlal Method in the Concept of Livelihood according to Imam Ibn Hazm's Perspective - Abdillah Afabih (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2023)
Islam has provided detailed regulations on marriage, from the marriage proposal (akad), agreement (akad), to the fulfillment of rights and obligations between husband and wife. All these statements are based on the Quran and Hadith. One of the husband's obligations towards his wife is to provide a living (support payments). Fiqh scholars unanimously agree that livelihood is the responsibility of the husband, regardless of his wealth, poverty, or middle ground. However, Imam Ibn Hazm has a unique and different viewpoint from the consensus of the scholars. He argues that the responsibility of providing a living actually shifts to the wife due to the husband's incapability. Based on this unique perspective, this research aims to analyze